Hubungan Kondisi Fisik Rumah Dengan Kejadian Tuberkulosis Paru Di Wilayah Kerja Puskesmas Ngemplak Boyolali - Syafri, Amalia Kartika; , Giat Purwoatmodjo, SKM., M.Kes; , Sri Darnoto S.KM M.PH (2015)
Tuberculosis is a direct contagion that caused by Mycrobacterium Tuberculosis. Houses without health requirement are one of risk factor of pulmonary tuberculosis. This study determines correlation between physical condition of houses with the event of pulmonary tuberculosis cases in work area of health center in Ngemplak Boyolali. This research is survey analytic study with case control studies. The population were patients with pulmonary TB casus 19 people and non pulmonary TB 19 people. Sampling technique applied total sampling. Analysis by using Chi-square test shows that there are correlations of lighting intensity with pulmonary TB cases p value = 0,003 and OR 8,125. No correlation between ventilation vast p value = 0,230, humidity p value = 0,319, population density constant, floor types constant, and wall types p value = 0,230. It is advised that relevant parties to participate in reducing pulmonary TB cases in work area of Health Center in Ngemplak Boyolali.